Nightlife Neighborhood Conflicts in Zurich. Innovative Practice of Governance involving Night Ambassadors - Alessia Cibin (Bollettino della Società Geografica Italiana, 2019)
The paper explores the role of night ambassadors in policy-making and their interaction with local authorities in the governance of the night-time economy. The study proposes an analytical framework based on Zurich as a case study, where policy measures have been adopted to address the conflict situation in Langstrasse nightlife district. In Zurich, the night ambassadors, the Bar and Club Commission and the Night City Council, as policy-making actors, share with the City Administration resources to create strategic alliances and intervene through informal and formal practices of governance and introduce a change in public policies. The City Administration coordinates horizontal governance arrangements with the new actors and all stakeholders, engaging them in the innovative institutional architecture: the Nachtleben [Nightlife] project. Furthermore, inclusive strategies transform night-time conflicts into negotiated agreements and acceptable solutions through a participatory process. The findings extend the literature on night-time economic planning and management through empirical evidence and are of value for night ambassadors and local authorities looking to improve the governance of night-time economy.